On the presence of fluvio-lacustrine deposits on the Pomarico hill (Matera): interpretation and engineering geology relevance - Lupo, Michele; Tecca, Pia Rosella; Genevois, Rinaldo (Italian journal of engineering geology and environment, 2024)
The village of Pomarico stands on top of a ridge between the valleys of the Bradano and Basento Rivers (Southern Italy) and is formed by the terms of the Plio-Pleistocene marine regressive cycle of the Bradanic Foredeep. In this area, the presence was observed of post-regressive alluvial facies in non-conformable contact with the underlying formation. This paper, based on an extensive engineering geological survey, reports the find of deposits rather different from those typical of the local stratigraphic series. The micropaleontological analyses indicate that these deposits are referable to Middle-Upper Pleistocene, suggesting a marsh or pond environment subsequent to the filling phases of the sedimentary basin and the following emersion. X-ray diffractometric analyses indicate a mineralogical composition similar to that of the Subapennine Clays, with a predominance of montmorillonite among clay minerals. The higher amount of montmorillonite results in significantly lower shear strength and higher compressibility values, entailing a different general behaviour with respect to natural or human-induced stresses. In order to highlight the relevance of their presence, numerical stability analyses were performed on a slope characterised by the presence of these deposits, also taking into account the seismicity of the area. The results seem to justify the surface creep phenomena and the small shallow landslides that characterise the area.